LITERATUR REVIEW: PENGARUH GERAKAN LITERASI SEKOLAH ( GLS ) MELALUI POJOK BACA DIGITAL ( POCADI ) TERHADAP PENINGKATAN LITERASI MEMBACA SISWA - Candi Budi Winanto; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The School Literacy Movement (GLS) is a strategic government effort to improve literacy culture in educational settings. However, its implementation often faces obstacles in terms of innovation and technology utilization. This article aims to determine the effect of the School Literacy Movement through the Digital Reading Corner on improving elementary school students' reading literacy. This study used a systematic literature review design, analyzing scientific articles published between 2015 and 2025 from Google Scholar, ResearchGate, and PubMed databases. Data were analyzed through reduction, classification, and synthesis to identify patterns and key themes from previous research findings. The study results indicate that the school literacy movement through the digital reading corner not only serves as a platform for students' creative expression but also improves their reading literacy skills. Digital Reading Corner is an innovative alternative for fostering reading interest based on digital technology in elementary schools. Furthermore, the digital reading corner activity also strengthens the literacy culture in schools by providing authentic, participatory, and contextual learning spaces. Based on the synthesis results, the digital reading corner can be categorized as an innovative and relevant strategy for improving reading skills in elementary school. Further research is recommended to integrate school literacy movements through digital reading corners to gain a deeper understanding of the influence of school literacy movements with digital literacy media on reading literacy skills in the digital learning era.